Komposisi dan Stratifikasi Vegetasi Pohon di Hutan Pendidikan Universitas Sumatera Utara, Tongkoh, Kabupaten Karo, Provinsi Sumatera Utara - Rehulina Rehulina; Agus Purwoko; Siti Latifah (Program studi Kehutanan USU, 2014)
The purpose of this research is to know the composition and stratification of vegetation at Education Forest of North Sumatra University, Tongkoh, Karo District, North Sumatra Province. This research conducted from May to June 2013. Data collection was using “lines method”. The sample plot techniques was a Purposive Sampling method with random start. The plot size was 20 m x 100 m. The results showed that found 73 species of 31 Families of trees, in which 5 Families with the most species of trees which Lauraceae (9 species), Meliaceae (7 specie), Myrtaceae (6 species), Fagaceae (5 species), and the Guttiferae, Moraceae, and respective Sapotaceae (each are 4 species). Education Forest of USU compiled by A stratum (62 individuals), stratum B (416 individuals), stratum C (2133 individuals), and stratum D (164 individuals) in a 2 ha area.Keywords: tforest compotiion, frest stratification, education forest of North Sumatra University (USU)